Correlation of clinical illness with viremia in Zika virus disease during an outbreak in Singapore - Ng, Deborah H. L. (2018)
Background: The first autochthonous Zika virus (ZIKV) outbreak in Singapore was detected in August 2016. We report an analysis of the correlation of clinical illness with viremia and laboratory parameters in this Asian cohort. Methods: We conducted a prospective longitudinal cohort study of patients with a positive blood ZIKV polymerase chain reaction (PCR) result who were admitted to Tan Tock Seng Hospital, Singapore, for isolation and management. Results: We included 40 patients in our study. Rash was present in all patients, while 80% (32/40) had fever, 62.5% (25/40) myalgia, 60% (24/40) conjunctivitis and 38% (15/40) arthralgia. The median duration of viremia was 3.5 days (IQR: 3–5 days). Patients with viremia of ≥4 days were more likely to have prolonged fever compared to those with viremia of less than 4 days (95% versus 63%, p=0.01), but had no significant correlation with other clinical signs and symptoms, or laboratory investigations. However, 21 patients (53%) had hypokalemia despite the absence of gastrointestinal symptoms. Conclusion: Although fever correlated with duration of viremia, 30% of patients remained viremic despite defervescence. Laboratory abnormalities such as leukopenia or thrombocytopenia were not prominent in this cohort but about half the patients were noted to have hypokalemia.